2014
DOI: 10.1556/aphysiol.101.2014.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of slow breathing: Does the pattern matter beyond the rate?

Abstract: Purpose: Patterned breathing allows standardized serial measurements of heart rate variability and baroreflex indices. The slow breathing augments these parameters, and regular exercises, including yoga breathing practices with even respiratory rates have long-term beneficial effects in cardiovascular diseases. The role of temporization of breathing phases, i.e. the ratio of expiration to inspiration, is not known. In order to characterize the hemodynamic and autonomic responses during varying breathing phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
(33 reference statements)
1
15
0
1
Order By: Relevance
“…After the third yoga session LF power and % LF also significantly increased. The long-term trend was that LF power and %LF significantly increased after the third yoga session compared to pre first session (baseline) [LF power: 1348 ± 1468 ms 2 The results from the 6 subjects who attended at least 4 yoga sessions did not show any significant differences before and after their individual yoga sessions except for the fourth yoga session, although trends were seen. This was probably due to the low number of subjects involved.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…After the third yoga session LF power and % LF also significantly increased. The long-term trend was that LF power and %LF significantly increased after the third yoga session compared to pre first session (baseline) [LF power: 1348 ± 1468 ms 2 The results from the 6 subjects who attended at least 4 yoga sessions did not show any significant differences before and after their individual yoga sessions except for the fourth yoga session, although trends were seen. This was probably due to the low number of subjects involved.…”
Section: Resultsmentioning
confidence: 86%
“…Maximal HRV is achieved when inhalation is accompanied by a marked increase in heart rate (HR), due to decreased parasympathetic and increased sympathetic activation, and exhalation results in the opposite response [1]. This coupling between breathing and HRV, respiratory sinus arrhythmia (RSA), is optimized when one breathes deeply and slowly [2]. Therefore just by controlling one's breath, one can increase HRV.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of slow breathing include beneficial changes in the Autonomic Nervous System (ANS) [5]. It was demonstrated that slow breathing increases parasympathetic cardiac modulation and reduces sympathetic cardiac control [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the immediate effects of slow breathing exercise, such as yoga exercise have been reported [18]. Paprika et al [19] investigated the relationship between slow breathing pattern and RR during yoga and the long-term effect in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%